Establishing Irrigation Thresholds for Furrow‐Irrigated Peanuts. Issue 1 (24th January 2019) - Leininger, S.D.; Krutz, L.J.; Sarver, J.M.; Gore, J.; Henn, A.; Bryant, C.J.; Atwill, R.L.; Spencer, G.D.
Abstract : Core Ideas: Irrigation scheduling in furrow‐irrigated peanut will improve by developing scientific thresholds. Use of soil moisture sensors will increase irrigation water use efficiency. Proper irrigation scheduling will maximize yield and economic profitability. Scheduling irrigations for furrow‐irrigated peanut ( Arachis hypogea L.) based on soil moisture potential could improve yield and net returns by ensuring adequate season‐long soil water availability. This research was conducted to determine if sensor‐based irrigation scheduling improves peanut yield, net returns above irrigation costs, and irrigation water use efficiency relative to FAO‐56, a water balance irrigation‐scheduling method that determines evapotranspiration using meteorological data and crop growth stage. The effects of irrigation scheduling (FAO‐56, ‐50 cbar, ‐75 cbar, ‐100 cbar, and non‐irrigated) on peanut yield, net returns above irrigation costs, and irrigation water use efficiency were investigated at Stoneville, MS on a Bosket very fine sandy loam (fine‐loamy, mixed, active, thermic Mollic Hapludalfs). Relative to non‐irrigated and FAO‐56, maintaining the soil moisture at ‐50 cbar improved peanut yield at least 12.7% and either had no effect during wet years or improved net returns above irrigation costs up to 20.7% during dry years ( P ≤ 0.0376). Maintaining soil moisture at ‐50 or ‐100 cbar either had no effect during wet years or increased irrigation water use efficiency by at least 5.3‐fold relative to FAO‐56 during dry years ( P = 0.0071). Our data indicate that peanut yield, net returns above irrigation costs, and irrigation water use efficiency are more consistently optimized in furrow‐irrigated environments by maintaining a season‐long irrigation threshold of ‐50 cbar.